2007
DOI: 10.1111/j.1464-410x.2007.06872.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of anaesthesia on the nitrergic pathway during the micturition reflex in rats

Abstract: RESULTSL-NAME injected i.v. decreased the intercontraction interval (ICI) in the awake but increased it in the anaesthetized rats. L-NAME injected i.t. increased the ICI in both states and these effects were not apparent after pre-treatment with resiniferatoxin. L-NAME injected i.c.v. decreased the ICI in the awake but increased i.t. in the anaesthetized rats. Intravesical L-NAME decreased the ICI in the awake but not in the anaesthetized rats. L-NAME administered i.v., but not i.t. or i.c.v., increased bladde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 28 publications
3
32
0
Order By: Relevance
“…NO donors can also affect bladder afferent neuron excitability by modulating Ca 2ϩ channels (Yoshimura et al, 2001) and when administered intravesically NO donors can suppress bladder hyperactivity induced by cystitis (Ozawa et al, 1999). To test the involvement of NO in the observed OxoM effects, the NOS inhibitor L-NAME (Masuda et al, 2007) was administered before OxoM. L-NAME alone at 5 mg/kg and 25 mg/kg (i.v.)…”
Section: The Inhibitory Effects Of Intravesical Oxom Involve Nomentioning
confidence: 99%
See 1 more Smart Citation
“…NO donors can also affect bladder afferent neuron excitability by modulating Ca 2ϩ channels (Yoshimura et al, 2001) and when administered intravesically NO donors can suppress bladder hyperactivity induced by cystitis (Ozawa et al, 1999). To test the involvement of NO in the observed OxoM effects, the NOS inhibitor L-NAME (Masuda et al, 2007) was administered before OxoM. L-NAME alone at 5 mg/kg and 25 mg/kg (i.v.)…”
Section: The Inhibitory Effects Of Intravesical Oxom Involve Nomentioning
confidence: 99%
“…7A). These effects lasted for Ͼ3-4 h and might be related to a block of NO mediated urethral smooth muscle relaxation and an increase in the urethral outlet resistance during micturition (Bennett et al, 1995;Masuda et al, 2007). Because 5 mg/kg L-NAME had fewer effects on CMG parameters (i.e., only the amplitude increased significantly from control; paired t test p Ͻ 0.05; n ϭ 9 rats), this dose was chosen for further studies.…”
Section: The Inhibitory Effects Of Intravesical Oxom Involve Nomentioning
confidence: 99%
“…Creatinine corrected NGF levels in urine were correlated with bladder volume at urge sensation in the controls but pathologic elevation of NGF levels in OAB patients at lower bladder capacity precluded the significant association of NGF expression with urgency sensation at full bladder capacity (Liu and Kuo, 2009). Bladder stretching in rodents is expected to be higher with the increased bladder capacity under anesthesia (Masuda et al, 2007). Therefore, cyclic stretching and contraction of bladder during CMG was expected to increase the expression of NGF and its receptor.…”
Section: Discussionmentioning
confidence: 99%
“…An NO scavenger, oxyhemoglobin, enhances bladder activity in the urothelium or suburothelially in normal conscious rats, suggesting that NO plays an important role in the regulation of afferent firing in the bladder . An overactive bladder is involved in excitability of bladder afferent C‐fibers . Several investigators have shown that the eNOS–NO–cGMP pathway could regulate the micturition reflex through the decrease in the excitability of bladder afferents .…”
Section: Luts/bph and Vascular Functionmentioning
confidence: 99%